2011
DOI: 10.1148/radiol.11091822
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Multiparametric MR Imaging for Detection, Localization, and Staging

Abstract: This review presents the current state of the art regarding multiparametric magnetic resonance (MR) imaging of prostate cancer. Technical requirements and clinical indications for the use of multiparametric MR imaging in detection, localization, characterization, staging, biopsy guidance, and active surveillance of prostate cancer are discussed. Although reported accuracies of the separate and combined multiparametric MR imaging techniques vary for diverse clinical prostate cancer indications, multiparametric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
432
3
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 620 publications
(453 citation statements)
references
References 131 publications
6
432
3
12
Order By: Relevance
“…(0.84 and 0.68, respectively in intermediate risk patients). 2 The mpMRI findings in the current patient by themselves were consistent with locally advanced disease, but these were clearly discrepant from the biopsy findings, which showed minimal cancer on the left side of the prostate, where the tumour was described as abutting the rectum. The patient was keen to avoid radiation, and, with chronic obstructive voiding symptoms due to a very large prostate, was most interested in surgical resection.…”
Section: Discussioncontrasting
confidence: 64%
“…(0.84 and 0.68, respectively in intermediate risk patients). 2 The mpMRI findings in the current patient by themselves were consistent with locally advanced disease, but these were clearly discrepant from the biopsy findings, which showed minimal cancer on the left side of the prostate, where the tumour was described as abutting the rectum. The patient was keen to avoid radiation, and, with chronic obstructive voiding symptoms due to a very large prostate, was most interested in surgical resection.…”
Section: Discussioncontrasting
confidence: 64%
“…Additionally, several studies have reported promising findings on the utility of DCE parameters in discriminating prostate cancer based on aggressiveness of the disease [91,92]. While DCE is an invaluable sequence in certain instances where other acquisition sequences will show artifact (i.e., for patients with hip replacements), DCE results might be confounded by the presence of prostatitis in the peripheral zone [1,5,93] or by mixed BPH nodules in the central gland [1,5,94,95].…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 99%
“…Since these characteristics are different for malignant and benign tissues, highresolution mpMRI provides valuable data that helps characterize the extent and biological behavior of prostate cancer. Owing to these capabilities, MR imaging of the prostate is increasingly being used to assist patients and clinicians to make management decisions [4][5][6][7][8].…”
mentioning
confidence: 99%
“…This is now possible by incorporating an MRI based imaging technique called multiparametric magnetic resonance imaging (mpMRI). MpMRI consists of complementing T1 and T2 weighted anatomic imaging with functional MR techniques including diffusion weighted imaging (DWI) and dynamic contrast-enhanced (DCE) imaging [4,5]. The imaging potential of mpMRI has undergone scrutinizing validation studies comparing mpMRI image sets directly with radical prostatectomy specimens that have been whole mounted in sections [6].…”
Section: Introductionmentioning
confidence: 99%